Use of a “super-child” approach to assess the vitamin A equivalence of Moringa oleifera leaves, develop a compartmental model for vitamin A kinetics, and estimate vitamin A total body stores in young Mexican children - López Teros, V.; Ford, J.L.; Green, M.H.; Tang, G.; Grusak, M.A.; Quihui-Cota, L.; Muzhingi, T.; Paz-Cassini, M.; Astiazaran-Garcia, H. (Elsevier, 2017)
Background: Worldwide, an estimated 250 million children <5 y old are vitamin A (VA) deficient. In Mexico, despite ongoing efforts to reduce VA deficiency, it remains an important public health problem; thus, food-based interventions that increase the availability and consumption of provitamin A–rich foods should be considered. Objective: The objectives were to assess the VA equivalence of 2H-labeled Moringa oleifera (MO) leaves and to estimate both total body stores (TBS) of VA and plasma retinol kinetics in young Mexican children.